Implementation Regulated in the Minister of Health Indonesian Republic Number 856/Menkes/ Sk/Ix /2009 about Hospital Emergency Installation in Bendan Pekalongan City Hospital - Anik Indriono Indriono; Tjahjono Kuntjoro; Joko Purwoko (Universitas Katolik Soegijapranata Semarang, 2019)
Hospitals in Indonesia are part of the health care system. The health services are started from Emergency Installation, which provided emergency service. An emergency is a life-threatening and disabling condition requiring fast, precise, effective and quality action. It can be achieved if the hospital has a service standard in the Emergency Installation. Emergency Installation Standards are set out in the Ministry of Health's Decree on Hospital Emergency Installation Standards. The research problems of this study were how the implementation of Emergency Installation standard and what factors affect the implementation. This study aimed to investigate the implementation of Hospital Emergency Installation Standards.This study is a qualitative study with the juridical sociological approach. The juridical aspect of this study is the regulation of health minister about Hospital Emergency Installation Standards, while the sociological aspect is the implementation of the regulation by the hospital. The legal material sources of the study include primary and secondary law materials. The data were collected through interviews and literature review.The results show that Emergency Installation Standards are regulated in Law number 44 of 2009 on Hospital. Specifically, Emergency Installation Standards have been regulated in the Minister of Health Indonesian Republic Number 856/Menkes/ SK/IX /2009 about Hospital Emergency Installation. On hospital Emergency Installation Standards. However, the reality in the field, the hospital has not implemented the regulation well, resulted in the poor quality of emergency services. Thus the patient's right to get service quality becomes neglected. The supporting factors of the implementation of Emergency Installation Standards were the high motivation of human resources, while the obstacles factors were less strategic of the hospital location, the constraints of medical equipment financing, and the lack of attention from hospital owners.